2015
DOI: 10.1057/fr.2014.59
|View full text |Cite
|
Sign up to set email alerts
|

Introduction: Feminism and the Politics of Austerity

Abstract: In the call for papers for this issue on the 'Politics of Austerity', we invited contributions that would draw on feminist analyses to interrogate the origins, modalities and differential effects of the economic crisis to which austerity has been a political response, as well as the political economy, material effects and discursive legitimations of 'austerity' itself. We were interested in exploring the ways in which the global ascendance of neo-liberal policies and discourses is enmeshed with the crisis in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…The global economic crisis and ensuing austerity measures have had a severe impact on women all around the world (Brah et al, 2015;Evans, 2016). Nor has the Spanish economic crisis that has lasted over 10 years been favourable to Spanish women.…”
Section: Reading Walls As Canvases For Resistancementioning
confidence: 99%
“…The global economic crisis and ensuing austerity measures have had a severe impact on women all around the world (Brah et al, 2015;Evans, 2016). Nor has the Spanish economic crisis that has lasted over 10 years been favourable to Spanish women.…”
Section: Reading Walls As Canvases For Resistancementioning
confidence: 99%
“…However, this collective national fantasy masks the uneven ways in which austerity is felt and experienced. Austerity measures have tended to have the most detrimental impact on those whose lives were already a struggle, and have thus deepened class, raced and gendered inequalities (Bassel & Emejulu, ; Brah et al., ; Durbin et al., ; Gillespie et al., ; Greer Murphy, ; Sandhu & Stephenson, ). In particular, existing inequalities have been exacerbated by severe cuts to state welfare.…”
Section: Introductionmentioning
confidence: 99%
“…This research is concerned with the features of that wider set of conditions particularly as these impacted upon the social reproduction of gender relations. Extensive feminist research has shown that the adoption of austerity as the ‘necessary’ approach to the financial crisis had significant gendered implications due to the fundamentally gendered nature of the spheres of finance, production and reproduction (Annesley & Scheele, ; Bargawi, Cozzi, & Himmelweit, ; Brah, Szeman, & Gedalof, ; Hozic & True, ; Karamessini & Rubery, ; Pearson & Elson, ). Austerity created a discursive field in which political and socioeconomic structures interacted with cultural constructions of gender (Allen, Mendick, Harvey, & Ahmad, ; Bramhall, ) and it is this gendered aspect of austerity that is of interest in this study.…”
Section: Introductionmentioning
confidence: 99%